Impressions of Hume - Frasca-Spada, Marina; Kail, P. J. E. (Peter J. E.) (Oxford : Clarendon, 2005)
'Impressions of Hume' presents new essays from leading scholars in different philosophical, historiographical, and literary traditions to which Hume made defining contributions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hume, David, -- 1711-1776.; Philosophy, Scottish -- 18th century